Management of Refractory Status Epilepticus and Profoundly Impaired Consciousness in Anti-NMDA Receptor Autoimmune Encephalitis - Indriasari, Indriasari; Alam, Mohamad Deny Saeful (Journal of Society Medicine, 2025)
Introduction: Autoimmune encephalitis is a major cause of non-infectious encephalitis and remains challenging to diagnose based solely on clinical presentation. Confirmation is particularly difficult in antibody-negative cases despite strong clinical suspicion, requiring comprehensive diagnostic workup. Case Description: A 25-year-old male presented with progressive altered mental status and seizures preceded by behavioral changes for 10 days. EEG showed no epileptiform activity, cerebrospinal fluid analysis excluded infection, and brain CT was unremarkable. Serum and CSF HSV IgG/IgM were non-reactive. Anti-NMDA receptor antibodies in CSF were strongly positive. The patient developed refractory status epilepticus requiring mechanical ventilation, deep sedation with propofol, and multiple anti-seizure medications including phenytoin. Empirical acyclovir was administered for 10 days without improvement. High-dose methylprednisolone (1 g/day for 5 days) was given as first-line immunotherapy but yielded no neurological recovery. On day 14, plasma exchange was initiated for three sessions, resulting in marked clinical improvement with recovery of consciousness and seizure control. Conclusion: This case highlights the critical importance of considering autoimmune encephalitis even when initial antibody results are pending or imaging is normal. Early escalation to second-line immunotherapy, particularly plasma exchange, can be lifesaving in anti-NMDAR encephalitis presenting with refractory status epilepticus and profound coma.